Pelatihan Pembuatan Ovitrap sebagai Upaya Menurunkan DBD di Nagori Pamatang Simalungun - Fitri Sari Saragih; Putra Apriadi Siregar (Shihatuna : Jurnal Pengabdian Kesehatan Masyarakat, 2021)
Ovitrap is one of the effective methods in controlling Aedes aegepty sp. Ovitrape is expected to be used by the community to reduce the incidence of dengue fever. The training using video media and leaflets is one way to increase the knowledge and skills of the community in making ovitrap. The purpose of this study was to determine the training in making ovitrap as an effort to reduce dengue hemorrhagic fever. This type of research is quasi-experimental research using a pretest-posttest design. The location in this study was conducted in Nagori Pematang Simalungun, Simalungun Regency. The sample of this research is the entire population (total sampling), namely all cadres who are still active as many as 40 people who are divided into two groups. This study will compare the knowledge and skills in making ovitrape in the film and leaflet media group. This study indicates that leaflet and film media can increase bad knowledge into good knowledge in making ovitrape. Leaflet and film media can improve skills in making ovitrape.Cadres have characteristics with the majority of the age 30-39 years old, complete junior high school education and work as housewives. Training using leaflets and video media can increase knowledge in making ovitrape. Leaflet and film media can improve skills in making ovitrape.